Edukasi Toilet Training pada Ibu dengan Anak Usia Toddler - Hairat, Ummul; Kelrey, Fathimah (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2024)
Parents, especially mothers who have toddler-aged children, are not yet optimal in providing toilet training education to their children. Based on the results of discussions held with parents, they said that their children were still using pempers and had never been given education by the community health center about toilet training, so the parents had no knowledge about toilet training. Based on this, we took the initiative to hold health education regarding toilet training education as a promotive and preventive effort for teenagers to improve their health status. The purpose of this activity is to hope that toddler-aged children can independently carry out toilet training. The methods is carried out by lectures, discussions and questions and answers while the media uses video. The results of this activity show an increase in participants' knowledge about toilet training for toddler-aged children. The conclusion of this activity is that toilet training education for mothers with toddler-aged children through health education can increase knowledge about toilet training in mothers.